2021
DOI: 10.1093/ejcts/ezab371
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump coronary artery bypass grafting is safe and effective in patients with severe left ventricular dysfunction

Abstract: OBJECTIVES Severe left ventricular dysfunction (LVD) is associated with increased risk following coronary artery bypass grafting (CABG). Due to a dearth of reports on the choice of CABG technique in patients with LVD, this study aims to compare the outcomes of off-pump CABG (OPCAB) and conventional CABG (ONCAB) in such patients. METHODS Retrospective single-centre propensity-matched analysis comparing early- and long-term out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
4
8
0
Order By: Relevance
“…Although several studies have been compared offpump and on-pump CABG in patients with low EF, the results are conflicting. Few studies showed that OPCABG was associated with lower risk of in-hospital mortality [2,25], and some showed that in-hospital outcomes were the same between OPCABG and ONCABG [31][32][33][34][35]. Regarding mid-and long-term outcomes, in line with our results, some studies showed similar risk between off-and on-pump procedures [33,34].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although several studies have been compared offpump and on-pump CABG in patients with low EF, the results are conflicting. Few studies showed that OPCABG was associated with lower risk of in-hospital mortality [2,25], and some showed that in-hospital outcomes were the same between OPCABG and ONCABG [31][32][33][34][35]. Regarding mid-and long-term outcomes, in line with our results, some studies showed similar risk between off-and on-pump procedures [33,34].…”
Section: Discussionsupporting
confidence: 88%
“…Few studies showed that OPCABG was associated with lower risk of in-hospital mortality [2,25], and some showed that in-hospital outcomes were the same between OPCABG and ONCABG [31][32][33][34][35]. Regarding mid-and long-term outcomes, in line with our results, some studies showed similar risk between off-and on-pump procedures [33,34]. There are several conducted studies in this field, although none of them consider individuals genomic and epigenomic profiles composed.…”
Section: Discussionsupporting
confidence: 87%
“… 6 , 21 However, it is important to note that learning curve, experience of the team, and case volumes do influence outcomes following these procedures. 22 Left ventricular dysfunction 6 , 23 , 24 and presence of diabetes mellitus, 6 , 25 , 26 , 27 , 28 , 29 as expected, influence long-term outcomes following MIDCAB operations. Nevertheless, female gender has not been found to affect survival rates following MIDCAB.…”
Section: Nonrobotic Midcabmentioning
confidence: 71%
“…13 In addition, the low number of distal anastomoses in the off-pump cohorts in the existing studies in the literature raises concerns about incomplete revascularization of heart teams. [9][10][11][12][13][14] In contrast, Diegeler et al showed that patients who underwent OPCAB had lower incidence rates of atrial fibrillation, stroke, and ventilation time, as well as shorter hospital stays, than those who underwent conventional CABG. 14 Despite concerns about the learning curve for this technique and the potential for fewer anastomoses, OPCAB may offer important advantages over traditional CABG for "subgroups of IHD patients".…”
Section: Off-pump Coronary Artery Bypass Grafting Surgery (Opcab)mentioning
confidence: 98%